The atmospheric circulation response to climate change-like thermal forcings in a simple general circulation model - Butler, Amy Hawes, author; Thompson, David W. J., advisor (Colorado State University. Libraries, 2009)
Temperature changes due to increased greenhouse gases and depleted stratospheric ozone are associated with robust changes in the large-scale atmospheric circulation. In this thesis we explore how these anthropogenically-driven temperature changes affect the atmospheric circulation. Our approach is to force a simple dry dynamical general circulation model (GCM) with idealized thermal forcings that resemble three key effects of greenhouse gas increases and stratospheric ozone depletion: warming at the polar surface, warming of the tropical upper troposphere, and cooling of the polar stratosphere.

We examine the responses in both transient and steady state experiments. The key findings are: (1) heating in the upper tropical troposphere drives a robust poleward shift of the storm tracks as well as a weakening of the stratospheric Brewer-Dobson circulation and an expansion of the Hadley cell circulation; (2) cooling in the polar stratosphere also drives a poleward shift of the storm track, but the tropospheric response is very sensitive to the level and depth of the forcing; (3) warming at the polar surface drives an equatorward shift of the storm track. The equatorward shift due to polar warming opposes the poleward shift due to tropical upper tropospheric warming mostly in the NH, where polar surface warming is more pronounced. Lastly, (4) the combined response to all three thermal forcings is quantitatively different from the sum of the responses to the individual forcings. Thus the response of the GCM to an individual thermal forcing is strongly dependent on the other thermal forcings applied to the model. The mechanisms of these responses are examined in transient simulations.
Keywords: atmospheric circulation; general circulation; thermal forcings; atmospheric sciences; climate change